The perception of postpartum mothers towards massage care during labor to reduce labor pain at PMB Hasna Dewi in 2023 - Andriyani, Rika; Hakameri, Cecen Suci; Damayanti, Ika Putri (Science Midwifery, 2024)
Labor begins when the uterus contracts and causes changes in the cervix. This process causes labor pain felt by the mother. This labor pain can cause the mother to choose another birth alternative to avoid labor pain, namely Sectio Caesarea delivery. In practice, midwives in providing birth care are expected to provide comfort during childbirth, for this reason it is necessary to make efforts to control pain during childbirth using non-pharmacological techniques, one of which is massage. Pregnant women often voice concerns that massage during pregnancy may cause complications or premature labor. Massage treatments that are too painful or too gentle have been reported to cause activation of the autonomic nervous system, which can prevent relaxing and stress-reducing effects. PMB Hasna Dewi is one of the midwife clinics that provides massage care during childbirth. From the results of interviews with PMB leaders, information was obtained that not all mothers agreed to be given massage care, one of the most common reasons was because they were uncomfortable and afraid. The results of this study show that postpartum mothers who received massage care to reduce pain during the labor process showed a positive perception, this can be seen from the positive experience felt by the mother during the labor process as well as the benefits felt by the mother of massage during the labor process, namely reducing pain during the labor process. opening period and provides comfort and relaxation during the labor process through distraction.